Investigation of energy efficiency of innovate thermal insulating materials and their influence on the building heat regime; MATEC Web of Conferences; Vol. 23 : Heat and Mass Transfer in the Thermal Control System of Technical and Technological Energy Equipment - Morozov М. N. Maksim Nikolaevich (2015, 2015)
Title screen